Liquidity Constraints and Investment in Transition Economies : The Case of Bulgaria - Budina, Nina (The World Bank, 1999)
January 2000 - In Bulgaria and other transition economies, liquidity constraints and hence access to external funds must be seen in the context of soft budget constraints and the financial system's failure to enforce the efficient allocation of funds. Liquidity constraints in Bulgaria may be seen as a sign of financial weakness. Budina, Garretsen, and de Jong use firm level data on Bulgaria to investigate the impact of liquidity constraints on firms' investment performance. Internal funds are an important determinant of investment in most industrial economies. The authors use a simple accelerator model of investment to test whether liquidity constraints are relevant in Bulgaria's case. Their estimates are based on data for 1993-95, before Bulgaria's financial crisis of 1996-97. It turns out that Bulgarian firms are liquidity-constrained and that firms' size and financial structure help to distinguish between firms that are more and less liquidity-constrained. In the authors' view, liquidity constraints in transition economies should be interpreted in different ways than those in industrial economies. In Bulgaria, liquidity constraints and hence access to external funds should be seen in the context of soft budget constraints and the financial system's failure to enforce the efficient allocation of funds. The relationship between liquidity constraints and firm characteristics may actually be the opposite of what is normally the case in industrial countries. In Bulgaria, lack of liquidity constraints may be a sign of financial weakness. This paper - a product of Macroeconomics and Growth, Development Research Group - is part of a larger effort in the group to study transition economies. The authors may be contacted at nbudina@worldbank.org, h.garretsen@bw.kun.nl or e.dejong@bw.kun.nl